2022
DOI: 10.1093/jtm/taac017
|View full text |Cite
|
Sign up to set email alerts
|

Global spread of a Japan-originated Delta lineage of SARS-CoV-2 after the Tokyo Olympics is most likely unrelated to the Olympics

Abstract: Highlight Participants of the 2021 Summer Olympics in Tokyo were required to adhere to strict health protocols, and there were no major local outbreaks within the separation bubbles. However, based on viral genomic data, we report that the Japan-specific Delta variants did spread out globally during or after the Olympics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“… [22] Jan. 5, 2022 Feb. 3, 2022 Japan Citizens in Japan Epidemiology Ex-post assessment na na Using synthetic control methods, this paper reported that COVID-19 infection in Tokyo likely increased due to the Tokyo 2020 Games, but the extent of the increase was difficult to estimate due to an overlap with the fifth wave. [23] Jan. 12, 2022 Feb. 8, 2022 Japan Citizens in other countries Epidemiology Ex-post assessment na na Variant analyses of SRAS-CoV-2 revealed that a Japan-originated Delta substrain was transmitted outside Japan in the wake of Tokyo 2020 Games but not likely related to the global spread of infection. [24] Sep. 11, 2021 Feb. 11, 2022 Japan Athletes and staff members Epidemiology Ex-post assessment Comprehensive measures Qualitative This paper reported the preparation and activities of clinics for spectators and athletes, which were managed by the Tokyo Organizing Committee of the Olympic and Paralympic Games.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… [22] Jan. 5, 2022 Feb. 3, 2022 Japan Citizens in Japan Epidemiology Ex-post assessment na na Using synthetic control methods, this paper reported that COVID-19 infection in Tokyo likely increased due to the Tokyo 2020 Games, but the extent of the increase was difficult to estimate due to an overlap with the fifth wave. [23] Jan. 12, 2022 Feb. 8, 2022 Japan Citizens in other countries Epidemiology Ex-post assessment na na Variant analyses of SRAS-CoV-2 revealed that a Japan-originated Delta substrain was transmitted outside Japan in the wake of Tokyo 2020 Games but not likely related to the global spread of infection. [24] Sep. 11, 2021 Feb. 11, 2022 Japan Athletes and staff members Epidemiology Ex-post assessment Comprehensive measures Qualitative This paper reported the preparation and activities of clinics for spectators and athletes, which were managed by the Tokyo Organizing Committee of the Olympic and Paralympic Games.…”
Section: Resultsmentioning
confidence: 99%
“…Evaluation of the transmission of Japan-originated substrains outside Japan using genome sequence analysis (2) [23] , [30] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the Delta variant was identifiable using this assay. New cases of infection with the Delta variant, such as the AY.29 sublineage ( 24 ), remain detectable in some countries, including Japan. The Delta variant increases the risk of hospitalization more than the Omicron variant ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the Delta variant was identifiable using this assay. New cases of infection with the Delta variant, such as the AY.29 sub-lineage (19), remain detectable in some countries, including Japan. The Delta variant increases the risk of hospitalization than the Omicron variant (20).…”
Section: Discussionmentioning
confidence: 99%